THE EFFECT OF USING ROUND ROBIN STRATEGY ON STUDENTS’ WRITING RECOUNT TEXT ABILITY (A STUDY AT THE TENTH GRADE STUDENTS OF SMA NEGERI 1 PINANGSORI IN 2018/2019 ACADEMIC YEAR) - Theresia Aghata Panggabean (JURNAL LINER (Language Intelligence and Educational Research), 2020)
The objectives of this research are to find out: 1) The extent of the application of round robin strategy in teaching writing recount text at the tenth grade students of SMA Negeri 1 Pinangsori, 2) The extent of students’ writing recount text ability before and after using round robin strategy at the tenth grade students of SMA Negeri 1 Pinangsori, 3) Whether there is a significant effect of round robin strategy on students’ writing recount text ability at the tenth grade students of SMA Negeri 1 Pinangsori. These research experimental method by pre-experimental design; one group pre-test post-test design. The population of this reserach is all of the tenth grade students of SMA Negeri 1 Pinangsori which consists of 284 students. The technique of sampling that used in this research is systematic sampling and the number of the sample consists of 30 students. In collecting the data, the researcher uses observation sheet to get the data of the application round robin strategy and test used to get the data of the recount text. The researcher uses statistical accounting to analysis the data by using ttest formula. Before using the round robin strategy the mean of score is 59.75 it is criterion as “Enough” while after using the round robin strategy the mean of score is 73 and it is categorized “Good”. Based on the data that had been analyzed, the result of the research showed that ttest is higher than ttable (ttest is 3.34 > ttable is 2.04) at 5% significances level with degree of freedom (df). It means that, there is a significant effect of round robin strategy on students’ writing recount text ability at the tenth grade students of SMA Negeri 1 Pinangsori in 2018/2019 Academic Year. So, the hypothesis is accepted.